Slum, Development in Yogyakarta City 1970-2000 - Marwasta, Djaka (Forum Geografi, 2001)
Slum, a dwelling that is statutorily unfit for human habitation, is still the big problem in, especially, cities of developing countries. This article highlights the development of slums in Yogyakarta City along 1970-2000, and itâs merely focused on spatial and socio-ecological development. The aims of the study is to analyze the distribution and development process of slum dwellings. Distribution of slum area is taken from interpretation of time-series aerial photos. The change of extent and distribution of slum is analyzed using Geographic Information System. To obtain the socio-economic characteristics of slum dwellers, the survey method is chosen. The respondent are selected randomly among head of household that represent each settlement units. Quality of settlement are determined by total score of 15 selected variables. The result shows that the first category of slum was increased 74.4 hectares from year 1970 to 2000, the second category was increased 47.6 hectares, and the third was 131.1 hectares. Nevertheless, the process of slum development in Yogyakarta City includes in "continuous" type, which slowly and long period of creation. Densification and aging process is two of the main causes of slum expansion. Distribution of slum unit were driven by rivers that next to city center. According to this research, itâs found out that the slum dwellers are characterized by the new migrant who had low income and education, working in the informal sector, and renting the house.